2020
DOI: 10.3390/ijms21051636
|View full text |Cite
|
Sign up to set email alerts
|

A New Human Blood–Retinal Barrier Model Based on Endothelial Cells, Pericytes, and Astrocytes

Abstract: Blood–retinal barrier (BRB) dysfunction represents one of the most significant changes occurring during diabetic retinopathy. We set up a high-reproducible human-based in vitro BRB model using retinal pericytes, retinal astrocytes, and retinal endothelial cells in order to replicate the human in vivo environment with the same numerical ratio and layer order. Our findings showed that high glucose exposure elicited BRB breakdown, enhanced permeability, and reduced the levels of junction proteins such as ZO-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 75 publications
1
54
0
1
Order By: Relevance
“…Several studies have shown that hyperglycemia represents the main risk factor contributing to the pathogenesis of diabetic retinopathy ( Engerman and Kern, 1986 ; Das et al, 2015 ; Eshaq et al, 2017 ). Furthermore, using a BRB model formed by retinal pericytes, astrocytes and endothelial cells, it has been recently reported that high glucose exposure elicits BRB breakdown, enhances BRB permeability and reduces the levels of junction proteins such as ZO-1 and VE-cadherin ( Fresta et al, 2020 ). Besides, elevated ROS as well as pro-inflammatory mediators (IL-1β, IL-6) and oxidative stress-related enzymes (iNOS, Nox2) have also been shown to be increased ( Fresta et al, 2020 ).…”
Section: Diabetic Retinopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that hyperglycemia represents the main risk factor contributing to the pathogenesis of diabetic retinopathy ( Engerman and Kern, 1986 ; Das et al, 2015 ; Eshaq et al, 2017 ). Furthermore, using a BRB model formed by retinal pericytes, astrocytes and endothelial cells, it has been recently reported that high glucose exposure elicits BRB breakdown, enhances BRB permeability and reduces the levels of junction proteins such as ZO-1 and VE-cadherin ( Fresta et al, 2020 ). Besides, elevated ROS as well as pro-inflammatory mediators (IL-1β, IL-6) and oxidative stress-related enzymes (iNOS, Nox2) have also been shown to be increased ( Fresta et al, 2020 ).…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Furthermore, using a BRB model formed by retinal pericytes, astrocytes and endothelial cells, it has been recently reported that high glucose exposure elicits BRB breakdown, enhances BRB permeability and reduces the levels of junction proteins such as ZO-1 and VE-cadherin ( Fresta et al, 2020 ). Besides, elevated ROS as well as pro-inflammatory mediators (IL-1β, IL-6) and oxidative stress-related enzymes (iNOS, Nox2) have also been shown to be increased ( Fresta et al, 2020 ). The major biochemical pathways involved in the BRB breakdown are the polyol pathway, the AGEs pathway, the PKC pathway and the hexosamine pathway.…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…Transendothelial electrical resistance measurements were performed once endothelial cultures of 3 models reached 95%-100% confluent. In Transwell (0.4 μ m pore size) cultures, TEER was conducted by a Millicell device (Millicell-ERS-2, MA, USA) and chopstick-like electrodes as described elsewhere [ 28 ]. One electrode was immersed in the upper chamber of Transwell and the other electrode in the lower chamber of a 24-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, numerous in vitro models were validated to mimic the in vivo conditions, which represent valuable tools to study the impact of high glucose at the BRB level as well as the trafficking between barrier sides or to develop novel molecules with beneficial effects against the BRB injury. An in vitro model of human BRB uses retinal pericytes, retinal astrocytes, and endothelial cells applicating the same in vivo layer order and the numerical ratio to mimic the physiological conditions [ 88 ]. After the assessment of the barrier, it was shown that glucose exposure induced BRB breakdown, increased barrier permeability, and reduced the expression of junctional proteins [ 88 ].…”
Section: Alternative 2d In Vitro Modelsmentioning
confidence: 99%